Analysis review on linguistic steganalysis - Syiham Mohd Lokman; Aida Mustapha; Azizan Ismail; Roshidi Din (Institute of Advanced Engineering and Science, 2020)
Steganography and steganalysis are essential topics for hiding information. Steganography is a technique of conceal secret messages by transmitting data through different domains. Its objective is to avoid discovery of secret messages. Steganalysis, meanwhile, is a method for locating the secret messages contained in the stego text. The objective of steganalysis is to find concealed data and to break the security of its domains. Steganalysis can be categorized into two types: targeted steganalysis and blind steganalysis. Steganography and steganalysis both have domains that are split into natural, also known as linguistic and digital media. There are three kinds of digital media which are picture, video and audio. The aim of this paper is to provide a survey on different linguistic steganalysis techniques used to find secret messages. This paper also highlighted two type of steganalysis method that are used in research and real practice. The discussion include findings on the most recent work on linguistic steganalysis techniques. This review hoped to help future research for improving and enhancing steganalytic capabilities.